2017
DOI: 10.3390/md15030066
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Inhibits PC-3 Xenograft Prostate Tumor Growth in Nude Mice

Abstract: Prostate cancer (PCa), the most common malignancy in men, is a major cause of cancer deaths. A better understanding of the mechanisms that drive tumor initiation and progression may identify actionable targets to improve treatment of this patient group. As a dietary carotenoid, astaxanthin has been demonstrated to exert beneficial effects against inflammation, cardiovascular disease, oxidative damage, or different cancer sites. This study used intragastric administration of astaxanthin to detect its role on tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…After treating PASMCs with Ruthenium Red and siTRPV3 the increased effect of TRPV3 on cell viability was significantly decreased. Meanwhile, we measured the expression of PCNA, which was an essential substance in the DNA synthesis phase of eukaryotic cells and an important index for evaluating the status of cell proliferation . We found that the PCNA expression was up‐regulated on hypoxic condition, but the effect was reduced in the presence of Ruthenium Red and siTRPV3.…”
Section: Discussionmentioning
confidence: 99%
“…After treating PASMCs with Ruthenium Red and siTRPV3 the increased effect of TRPV3 on cell viability was significantly decreased. Meanwhile, we measured the expression of PCNA, which was an essential substance in the DNA synthesis phase of eukaryotic cells and an important index for evaluating the status of cell proliferation . We found that the PCNA expression was up‐regulated on hypoxic condition, but the effect was reduced in the presence of Ruthenium Red and siTRPV3.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies using cancer cell lines and preclinical animal tumour models have convincingly demonstrated the potent anti-proliferative and proapoptotic effects of AXT. 15,22,23,34 However, inconsistencies were also reported on the efficacy of AXT between cell-based assays and in vivo studies. The lack of consistency has been largely ascribed to the low bioavailability and weak targeting ability of AXT.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, patients with BPH seem to have lower abundances of Lachnospiraceae compared to patients with prostate cancer . Further, increased levels of both faecal Lactobacillus and Lachnospiraceae have been shown to be associated with reduced prostate tumour in the mouse .…”
Section: Discussionmentioning
confidence: 99%